A phenomenological study of online assessment during a pandemic crisis: Insights from Malaysia, Lithuania, and Spain - Annamalai, Nagaletchimee; Ramírez García, Antonia; Mažeikienė, Viktorija; Alqaryouti, Marwan Harb; Rashid, Radzuwan Ab; Uthayakumaran, Arulselvi (Frontiers in Psychology, 2022)
Many countries, including Malaysia, Lithuania and Spain, shifted to online assessment during the COVID-19 pandemic. The present study conducted a qualitative case study with 18 undergraduate students from these three countries to probe insights into the online assessment experienced by them. Data were interpreted from the perspective of the expectancy-value theory of motivation proposed by Wigfield and Eccles (1992), which emphasises intrinsic, attaintment, utility, and cost values. The findings revealed that students were motivated to complete their assessment since they experienced flexibility in the assessment in addition to effective assessment guidelines. These positive experiences were related to intrinsic and attaintment values; however, they were also demotivated when they were stressed with the online assessments indicating high cost value. The study also reported on inefficient assessments experienced by students. Utility value is not evident in this study. Hence, the educators need to consider utility values when preparing the online assessments. The pedagogical implication stresses the importance of checklist, mock exams, alternative assessment (Plan B) and video demos for effective assessment. Efforts from instructors are needed to encourage utility values since online assessment do not have a rigid format to assess students.Instructors and e-learning policymakers to consider potential benefits and challenges when encouraging online assessment, especially during crisis time.